Brivaracetam, a selective high‐affinity synaptic vesicle protein 2A (SV2A) ligand with preclinical evidence of high brain permeability and fast onset of action. (10th December 2015) - Nicolas, Jean‐Marie; Hannestad, Jonas; Holden, Daniel; Kervyn, Sophie; Nabulsi, Nabeel; Tytgat, Dominique; Huang, Yiyun; Chanteux, Hugues; Staelens, Ludovicus; Matagne, Alain; Mathy, François‐Xavier; Mercier, Joël; et al.
Summary: Objective: Rapid distribution to the brain is a prerequisite for antiepileptic drugs used for treatment of acute seizures. The preclinical studies described here investigated the high‐affinity synaptic vesicle glycoprotein 2A (SV2A) antiepileptic drug brivara‐cetam (BRV) for its rate of brain penetration and its onset of action. BRV was compared with levetiracetam (LEV). Methods: In vitro permeation studies were performed using Caco‐2 cells. Plasma and brain levels were measured over time after single oral dosing to audiogenic mice and were correlated with anticonvulsant activity. Tissue distribution was investigated after single dosing to rat (BRV and LEV) and dog (LEV only). Positron emission tomography (PET) displacement studies were performed in rhesus monkeys using the SV2A PET tracer [ 11 C]UCB‐J. The time course of PET tracer displacement was measured following single intravenous (IV) dosing with LEV or BRV. Rodent distribution data and physiologically based pharmacokinetic (PBPK) modeling were used to compute blood–brain barrier permeability (permeability surface area product, PS) values and then predict brain kinetics in man. Results: In rodents, BRV consistently showed a faster entry into the brain than LEV; this correlated with a faster onset of action against seizures in audiogenic susceptible mice. The higher permeability of BRV was also demonstrated in human cells in vitro. PBPK modeling predicted that, following IV dosing to human subjects, BRV might distribute to the brain within a few minutes compared with approximately 1 h for LEV (PS of 0.315 and 0.015 ml/min/g for BRV and LEV, respectively). These data were supported by a nonhuman primate PET study showing faster SV2A occupancy by BRV compared with LEV. Significance: These preclinical data demonstrate that BRV has rapid brain entry and fast brain SV2A occupancy, consistent with the fast onset of action in the audiogenic seizure mice assay. The potential benefit of BRV for treatment of acute seizures remains to be confirmed in clinical studies.